2020
DOI: 10.1088/1361-648x/aba674
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical prediction of superconductivity in monolayer h-BN doped with alkaline-earth metals (Ca, Sr, Ba)

Abstract: We investigated the possibility of superconductivity in monolayer hexagonal boron nitride (h-BN) doped using group-1 (Li, Na, K) and group-2 (Be, Mg, Ca, Sr, Ba) atoms via ab initio calculations. Consequently, we reveal that Sr-and Ba-doped monolayer h-BN and Ca-doped monolayer h-BN with 3.5% tensile strain are energetically stable and become superconductors with superconducting transition temperature (Tc) values of 5.83, 1.53, and 10.7 K, respectively, which are considerably higher than those of Ca-, Sr-, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The gating approach is similar to the case for biaxialtensile-strained and doped graphene (4.0× 10 14 holes cm −2 ) which shows the superconductivity with T c ∼30 K [21]. By means of chemical doping of Ca, Ba, and Sr atoms, one may theoretically obtain the superconductivity in monolayer h-BN with T c ranging from ∼1 K to 10 K [22]. The bilayer h-BN with an intercalated Li atom has also been predicted to show the superconductivity with different T c (< 25 K) [23,24].…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The gating approach is similar to the case for biaxialtensile-strained and doped graphene (4.0× 10 14 holes cm −2 ) which shows the superconductivity with T c ∼30 K [21]. By means of chemical doping of Ca, Ba, and Sr atoms, one may theoretically obtain the superconductivity in monolayer h-BN with T c ranging from ∼1 K to 10 K [22]. The bilayer h-BN with an intercalated Li atom has also been predicted to show the superconductivity with different T c (< 25 K) [23,24].…”
mentioning
confidence: 70%
“…Within this range of hole density, both the electron DOS and λ get enhanced with the increase of n. This result shows the correlation between EPC, DOS, and robust superconductivity [41]. In our calculations for T c , we adopted µ * = 0.13 which was used in [16] (note also that values of µ * are ranged from 0.10 to 0.14 [20,22,23]). It is important to notice that doping with higher carrier densities would cause the lattice to become unstable at 1.6× 10 14 holes cm −2 (see Fig.…”
mentioning
confidence: 91%
“…It is worthwhile to mention that in a recent experimental work, it was found that T C = 3.8 ± 0.1 K the Kintercalated black phosphorene bilayer [42]. The critical temperature for P-Ca-P compound is almost comparable with the bulk intercalation compound CaC 6 [65,66], and hBN-Ca [67]. Finally, the last compound P-Sr-P gives a superconducting transition temperature that is higher compared with the one obtained for monolayer h-BN doped with T C = 5.83 K [67].…”
Section: Epc and Superconductivity Propertiesmentioning
confidence: 85%
“…We confirmed that even subsequent annealing did not promote intercalation of Ca, but desorption from the surface at 870 K. Although Ca is predicted to cause a larger shift than Cs based on its divalent nature, 8 it did not show intercalation or ionization in our experiments. A possible reason for that is given by a theory, 16 where the tensile strain of hBN is necessary to make the adsorption of Ca stable.…”
mentioning
confidence: 99%